Hysteresis in centrosymmetric CuPbI3perovskite halide: Apolar dielectric or orientable dielectric? - Bharti P.C.; Jha P.K.; Jha P.A.; Singh P. (My University, 2025)
We demonstrated the change in polarization behaviour at the surface/interface before and after light through Havriliak-Negami equation of lesser known CuPbI3. We have synthesized CuPbI3 through cold sintering technique and the polarization mechanisms are altered by increasing (cold) sintering temperature. The structure of CuPbI3 was not known and we predicted it to be hexagonal (R3¯m) with 21R prototype representation. The hysteresis is reported to be affected by ferroelectricity (reorientable dipoles with non-centrosymmetry), to inspect this a centrosymmetric CuPbI3 is taken. In spite of centrosymmetry, we observed that the hysteresis area and shape of IV curve in AM 1.5 G sunlight shows the drastic variation with the change in polarization behaviour. Our experimental results suggest that apolar dielectric behaviour is the cause of I-V hysteresis rather than robust ferroelectric polarization (which was absent in the present case). © 2021 IOP Publishing Ltd.